Video head impulse testing in patients with benign paroxysmal positional vertigo. (1st December 2020) - Saltürk, Ziya; Yetişer, Sertaç
Abstract: Background: Vestibulo-ocular reflex (VOR) function is expected to be normal in patients with benign paroxysmal positional vertigo (BPPV) during sudden head rotations. Aim: The aim of this study is to analyze VOR by video head impulse test (vHIT) in patients with BPPV in order to determine the potential value of clinical application of vHIT in BPPV. Material and method: Sixty patients with BPPV were included for the study from out-patient admissions. The main outcome measures were the gain of VOR, gain asymmetry, and refixation saccades. Fifteen healthy subjects with no history of dizziness were selected as normal control. Results: Mean VOR gain during lateral head impulse in patients with geotropic type LC BPPV was 0.85 ± 0.22. Mean VOR gain during lateral head impulse in patients with ageotropic type LC BPPV was 0.78 ± 0.16. Fourteen patients with PC BPPV (35%; 40/13) had low gain during ipsilesional head impulses. Seven patients had low gain during counterlesional head impulses. Mean VOR gain during vertical head impulse in patients with PC BPPV was 0.73 ± 0.24. Nine patients with posterior canal BPPV (25%; 9/40) and 2 patients with LC BPPV (11%; 2/18) had corrective saccades. None of the results showed significant difference in comparison to control group. Conclusion and significance: VHIT analysis demonstrated that VOR function was normal on the BPPV side.